RISK MANAGEMENT IN COMPANY BUSINESS TRANSFORMATION (STUDY CASE: PT BADAK NGL) - Hasurungan, David
PT Badak Natural Gas Liquefaction (NGL) is an oil and gas company located in Bontang, East Kalimantan. First established in 1977, PT Badak NGL has more than 43 years of experience in liquefying natural gas produced by Production Sharing Contractors (PSC) in East Kalimantan region. Since 2001, natural gas supply has continuously declined and forced PT Badak NGL to reduce their train operation from 8 trains to 2 trains. Facing these challenges, PT Badak NGL management decided to transform the company from cost center to become profit company. This transformation is done by increasing the current business portfolio with new business portfolios, such as: Regasification Plant, Small Scale LNG Terminal, LNG/LPG Bunkering, and Commercial Services. Risk assessment will help PT Badak NGL Management in identifying, prioritizing, and managing the risks that can be occurred in their new business. Based on ISO 31000:2018, risk management has three elements: principle, framework, and process. First step in the risk management process is to identify the risks that may occur in PT Badak NGL. Risk identification is done by interviewing and discussing with the responsible peoples, external analysis, internal analysis, and SWOT (Strength, Weakness, Opportunity, and Threat) analysis. After performing the risk identification, risk measurement using Analytical Hierarchy Process (AHP) is done to defined risk on PT Badak NGL business. Evaluating the risk is done to formulate the response for the risk. Last, implementation plan is developed for PT Badak NGL. Based on the results, PT Badak NGL has 6 risk categories, including Business Risk, Financial Risk, Operational Risk, Reputational Risk, Legal Risk, and Project Design Risk. Based on the risk mapping, there is no risk categorized in the critical risk level. There are 9 risks categorized as high-risk level, 24 risks categorized as medium risk level, and 7 risks categorized as low risk level. The implementation plan and the schedule were formulated for high-risk levels. The action plan consists of a strategy in how to address risk, what action to be taken, and who is responsible for action to reduce the likelihood and impact of these risks. Future research is proposed in developing risk assessment on project construction phase.